The Berenstain Bears Thanksgiving blessings - Berenstain, Mike, 1951- (Grand Rapids, Michigan : Zonderkidz, 2013)
On their way to Grizzly Gramps' and Grans' house for Thanksgiving dinner, Papa reminds his cubs that Thanksgiving Day is about more than just food.
Keywords: Gratitude -- Juvenile fiction; Thanksgiving Day -- Juvenile fiction; Bears -- Juvenile fiction; Christian life -- Juvenile fiction; Gratitude -- Fiction; Thanksgiving Day -- Fiction; Bears -- Fiction; Christian life -- Fiction